Identification of a Potential Common Ancestor for Mammalian Cross-Presenting Dendritic Cells in Teleost Respiratory Surfaces - Soleto, Irene; Fischer, Uwe; Tafalla, Carolina; Granja, Aitor G. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are highly specialized antigen presenting cells that bridge innate and adaptive immune responses in vertebrates, being key modulators in the initiation of specific responses. Although teleost fish present the main elements of a fully developed adaptive immune system, not many studies have focused on identifying specific DC subsets in teleost species. Previous work from our group identified in rainbow trout (Oncorhynchus mykiss) skin a DC subpopulation co-expressing CD8α and MHC IIβ on the cell surface. Interestingly, these CD8+ DCs expressed common unique markers of mammalian cross-presenting DCs, a DC subset with an important role in antigen presentation and activation of CD8+ T cytotoxic lymphocytes. In the current study, we have identified a similar DC subset in rainbow trout gills that also transcribes molecules uniquely expressed on diverse mammalian cross-presenting DC populations such as CD8, CD103, CD141, Batf3, IRF8 and TLR3. Hence, we have undertaken a broad phenotypic and functional characterization of this new DC subset that includes the confirmation of novel capacities for DCs in teleost, such an IgM binding capacity and responsiveness to CD40 ligand (CD40L). Furthermore, our results show that in gills, this DC subset shows some different phenotypic and functional characteristics when compared to their homologues in the skin, suggesting an adaptation of the cells to different mucosal tissues or different maturation status depending on their location. Our findings contribute to increase our knowledge on fish cross-presenting DCs, an important cell population to take into account for the future design of mucosal vaccination strategies.